Animated Films made in Spain: Dubbing and Subtitling of Cultural Elements - Fuentes-Luque, Adrián; López-González, Rebeca Cristina (Íkala, Revista de Lenguaje y Cultura, 2020)
Although Translation Studies have dealt with the translation of animated films into the various modes of audiovisual translation (dubbing, subtitling, etc.), such studies have focused almost exclusively on films translated from English into other languages. So far, there are hardly any studies analysing the translation into English of cultural elements contained in animation films produced in Spanish language. This article analyses the dubbing and subtitling of three animation films produced in Spain —Planet 51 (2009), Las aventuras de Tadeo Jones (2012), and Atrapa la bandera (2015), with the aim of finding out which cultural elements have been included in the original Spanish version of each of these productions and how they have been translated into the English dubbed and subtitled versions. To this end, a working methodology was developed based on the classification of cultural elements and on the various translation strategies used for dubbing and subtitling cultural content. Results show that almost half of the cultural elements compiled demand the services of a translator. These cases have been classified under the ‘Environment’ category and the ‘Cinematography’ subtype. This final subtype has a major impact on the corpus.